La carga de la prueba en el seguro de transporte de carga terrestre (2015)
The insurance contract road freight transport in Colombia, in the light of Article 1077 of the Commercial Code, indicates that the insured shall demonstrate the occurrence of the claim and the amount of loss, if applicable. Thus at the time of the claim by the insured, with the insurer, for the respective payment of compensation, but should demonstrate the two circumstances mentioned in Article 1077 of the Commercial Code.